ANALYSIS OF INFORMATION SYSTEM MODERNIZATION IN IMPROVING INDIVIDUAL TAXPAYER COMPLIANCE AT KPP PRATAMA SUKOMANUNGGAL SURABAYA - Ayu Praditias Sumono Putri; Arief Rahman; Ali Muhdor; Fitriyah Kusuma Devi (LPPM STIE YKPN Yogyakarta, 2025)
The Directorate General of Taxes is carrying out new innovations in the field of taxation, namely by utilizing information technology, resulting in the launch of computer taxation systems such as modernization, e-filing to make it easier for taxpayers to report annual tax returns. This research aims to evaluate the impact of implementing modernization of the tax system, especially the e-filing feature, on increasing individual taxpayer compliance at KPP Pratama Sukomanunggal Surabaya. Using a descriptive qualitative approach, this research collects data through interviews, observation and documentation. The research results show that modernization of the tax system, especially e-filing facilities, has made a significant contribution to increasing taxpayer compliance in submitting Annual Tax Returns (SPT). Ease of access, time efficiency and accuracy of data produced by the e-filing system are the main factors driving increased compliance.